On Marital Contracts in the Tešanj Kadiluk in the Second Half of the 18th Century (Prilozi za orijentalnu filologiju, 2021)
Marriage was one of the many matters presided over by kadis in their districts. This paper examines the matter of marriage through cases from the Tešanj kadiluk dating from the second half of the 18th century. A total of 120 written marriage contracts were analysed. They reveal how marriages were concluded, who the parties to the contracts were, as well as other particularities found in the records of the Tešanj kadi. Marriage was concluded by a kadi or naib and in extraordinary circumstances by an authorised imam from one of the jamaats. However, “authorising of imam” was rarely done in practice.The bride and groom were rarely present at the court for the conclusion of marriage. The ceremony usually involved proxies (vekil) and always required witnesses to confirm their legitimacy of representation for the purpose of marriage. There are also records of kadis or their naibs marrying non-Muslims and Roma, widows, though these are very rare. In order to better understand these issues, we sometimes made comparisons with other areas in the same or similar time period. The comparisons showed that very few marriages between non-Muslims before a kadi were recorded in the Tešanj kadiluk, as opposed to Mostar.Mehr is a mandatory and indispensable element of concluding a marriage for Muslims and non-Muslims alike. The mehr amount depended on many factors, foremost among them being the social status of the parties involved. The lowest mehr amounted to a symbolic 120 akçes, while the highest documented mehr was 12000 akçes. In most cases, mehr amounts were equal to the annual income of an official (an imam, mualim, etc.), which represented a generous guarantee for the woman in the event of divorce. In the documented cases of non-Muslim marriages from the Tešanj kadiluk, the dower was symbolic and purely formal in a number of marriages, which was not the practice in other regions that we compared with this kadiluk.